Clinical Significance of Breast Cancer Stem Cells - Dias, Kay (My University, 2014)
Tumour initiation and progression is thought to be driven by a small population of tumor initiating cells (TICs) or cancer stem cells (CSCs), which have the capacity to migrate and cause metastases and contribute to tumour relapse. These cells possess properties that are similar to those of normal tissue stem cells, which include the capacity to undergo self-renewal as well as the capacity to give rise to more differentiated progenitor cells, which comprise the bulk of the tumour cell population. Thus far, the clinical significance of these cells in breast cancers has not been extensively explored with regard to their relationship with tumour pathology or patient survival. In this thesis we evaluate the presence of these cells in terms of clinicopathological tumour characteristics and patient outcome, as well as assess potential markers of breast CSCs for prognostic significance. Through the quantification of breast CSCs in primary breast tumours using in vivo xenografts assays we show that their presence correlates with aggressive tumour characteristics. In addition, we propose that markers of breast CSCs may differ based on the molecular subtype of the tumour, and that these markers have prognostic significance in patients.
Keywords: Breast Cancer; Cancer Stem Cells